2022
DOI: 10.1186/s40364-022-00431-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk variants related to malignant tumors in children with birth defects by whole genome sequencing

Abstract: Background Children with birth defects (BD) are more likely to develop cancer and the increased risk of cancer persists into adulthood. Prior population-based assessments have demonstrated that even non-chromosomal BDs are associated with at least two-fold increase of cancer risk. Identification of variants that are associated with malignant tumor in BD patients without chromosomal anomalies may improve our understanding of the underlying molecular mechanisms and provide clues for early cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In a previous study we reported on genetic variants associated with pediatric cancer in BD children [ 2 ]. Whether these variant/biomarkers are predictive of cancer incidence in BD children remains unknown.…”
mentioning
confidence: 99%
“…In a previous study we reported on genetic variants associated with pediatric cancer in BD children [ 2 ]. Whether these variant/biomarkers are predictive of cancer incidence in BD children remains unknown.…”
mentioning
confidence: 99%